Dampak Kebijakan Harga Acuan Pembelian Pemerintah dan Harga Input terhadap Produksi Jagung di Indonesia - Munthe, M Taufiqurrohman; Asaad, Mhd; Karo Karo Sitepu, Rasidin (Jurnal Sosial Ekonomi Pertanian, 2025)
Maize is a strategic food commodity in Indonesia, second only to rice, primarily serving as a key input for the animal feed industry. The government has implemented input subsidy policies (fertiliser and seed) along with the establishment of a Government Purchase Reference Price (HAP) to protect farmers from price volatility. This study aims to analyse the impact of HAP and input subsidy policies on national maize production. An econometric model was developed using a system of simultaneous equations, comprising 13 structural equations and 2 identities, to capture supply and demand behaviours (household consumption, feed industry, and food industry), input utilisation, and maize price formation. Parameter estimation was conducted using the Two-Stage Least Squares (2SLS) method with time series data from 1990 to 2023. Policy simulations were performed to evaluate the effects of a 5% increase in fertiliser subsidies, seed subsidies, and HAP. Simulation results indicate that an increase in fertiliser subsidies significantly raises maize production and reduces domestic prices, while an increase in HAP leads to higher maize prices and production but reduces consumption. Seed subsidies had a relatively smaller impact on production. The combination of input subsidy and HAP policies resulted in a maize production surplus, highlighting the need for enhanced output absorption efforts. While input subsidies effectively stimulate production, they may suppress market prices; conversely, HAP policy increases production incentives but lowers demand. The government should strengthen domestic maize utilisation programmes to ensure optimal absorption of increased output and develop buffer mechanisms to maintain price stability